Bach, the fencing master: Reading aloud from the first three cello suites - Bijlsma, Anner 1934-2019 (Amsterdam Bijlsma's Fencing Mail, 1998)
Includes transcriptions by the author of the first three suites for violoncello by J.S. Bach.Christian symbolism in the first three preludes of Johann Sebastian Bach's Six suites for cello solo / by Gé Bartman ([4] p.) in pocket at end.